Britain - Osborne, John, 1907-1981. (New York, Time, 1967)
A comprehensive survey of social, political, and economic life in Great Britain.
Bibliography: p. 169.
Keywords: Great Britain -- Civilization; Great Britain -- Pictorial works; Great Britain -- History; Great Britain -- Description and travel; Grande-Bretagne -- Histoire; Grande-Bretagne -- Descriptions et voyages